2016
DOI: 10.1155/2016/3964806
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression and Anxiety amongst Cancer Patients in a Hospital Setting: A Cross-Sectional Study

Abstract: Background. The biomedical care for cancer has not been complemented by psychosocial progressions in cancer care. Objectives. To find the prevalence of anxiety and depression amongst cancer patients in a hospital setting. Design and Setting. This cross-sectional study was conducted at the tertiary care hospitals Shifa International Hospital Islamabad and Nuclear Medicine, Oncology, and Radiotherapy Institute [NORI]. Patients and Methods. 300 patients were interviewed from both the outpatient and inpatient depa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
23
4
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 13 publications
9
23
4
4
Order By: Relevance
“…The HADS instrument consists of alternating seven general anxiety items (1,3,5,7,9,11,13) with seven depression items (2,4,6,8,10,12,14). The HADS was scored on a four-point Likert scale ranging from zero to three.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HADS instrument consists of alternating seven general anxiety items (1,3,5,7,9,11,13) with seven depression items (2,4,6,8,10,12,14). The HADS was scored on a four-point Likert scale ranging from zero to three.…”
Section: Methodsmentioning
confidence: 99%
“…The previous studies reported that cancer symptoms, such as constant pain and change in body image, had an impact on the development of depression. The pain was associated with depression among cancer patients in China, [14] Oncology, and Radiotherapy Institute [NORI]. Patients and Methods.…”
Section: Clinical and Cancer Factors Associated With Anxiety And Deprmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown by numerous studies earlier, patients with cancer have lower levels of mental health and experience higher levels of hopelessness, depression, anxiety, and other mental problems when compared with healthy individuals [24][25][26][27][28]. Furthermore, their self-confidence, due to their disease, surgery, or mastectomy, which damage their beauty and femininity, decreases.…”
Section: Discussionmentioning
confidence: 99%
“…The many complaints and treatments that need to be carried out have an impact on physical, mental, and financial. In addition to pain, fatigue, nausea and vomiting, sleep disturbances, and social barriers, cancer patients can experience anxiety, and depression 2 . These issues can cause patient comfort to be disturbed 3 .…”
Section: Introductionmentioning
confidence: 99%